2004
DOI: 10.1093/humupd/dmh020
|View full text |Cite
|
Sign up to set email alerts
|

Experimental approaches to the study of primordial germ cell lineage and proliferation

Abstract: New information regarding primordial germ cell (PGC's) segregation and proliferation over the last decade is reviewed. Advances have been obtained in the mouse but current knowledge of human PGC's remains scant. Questions still fully or partially unresolved about the emergence of the germline in mammals are addressed. (i) When and where is the germ line set aside in the embryo? (ii) How is the germ line segregated from the somatic lineages? (iii) Which factors guide PGC's to the gonadal ridges? (iv) Which fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 97 publications
2
44
0
Order By: Relevance
“…LIF has been widely studied as a media additive important for the maintenance of ES cells in a self-renewing, undifferentiated state [21][22][23][24]. However, based on several reports demonstrating the importance of LIF not only in the survival and self-renewal of PGCs [25][26][27]44], but also in the maturation of oocytes and ovarian follicles [26,28,31,45], we decided to study its role in the formation of germ cells from ES cells in vitro. We found that LIF, when added to the media of ES cells differentiating in the absence of a MEF monolayer, significantly increased not only the number of eGFP-positive oocyte-like cells, but also the expression of oocyte specific genes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…LIF has been widely studied as a media additive important for the maintenance of ES cells in a self-renewing, undifferentiated state [21][22][23][24]. However, based on several reports demonstrating the importance of LIF not only in the survival and self-renewal of PGCs [25][26][27]44], but also in the maturation of oocytes and ovarian follicles [26,28,31,45], we decided to study its role in the formation of germ cells from ES cells in vitro. We found that LIF, when added to the media of ES cells differentiating in the absence of a MEF monolayer, significantly increased not only the number of eGFP-positive oocyte-like cells, but also the expression of oocyte specific genes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…PGC growth is sustained by a variety of soluble and membrane-bound growth factors (for a review, see De Felici et al, 2004). These factors prevent PGC apoptosis and/or stimulate their proliferation.…”
Section: Pgc Proliferationmentioning
confidence: 99%
“…PGCs undergo two mitotic blocks: the first at 7.5 up to 9.0 dpc in G 2 both in the female and male (Seki et al, 2007) and the second at 13.5-14.5 dpc in G 1 /G 0 in the male (Western et al, 2008). Mutations affecting PGC proliferation as well some intracellular players controlling their mitotic cycle have been identified (De Felici et al, 2004;Sorrentino et al, 2007;Western et al, 2008;Spiller et al, 2009) (Fig. 4).…”
Section: Pgc Proliferationmentioning
confidence: 99%
“…Follicular endowment begins with the allocation of a founder population of primordial germ cells (PGCs), which are the embryonic precursors of adult gametes, the male spermatozoa, and female oocyte (reviewed in Starz-Gaiano & Lehmann 2001). PGCs are allocated from precursor cells in the proximal epiblast during gastrulation, with the first PGCs identifiable around embryonic day (E)7.2 in mice, at the base of the allantois (reviewed in Ginsburg et al 1990, Lawson & Hage 1994, Tam & Zhou 1996, De Felici et al 2004.…”
Section: Introductionmentioning
confidence: 99%